(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article presents an in-depth study of the comparability of thermal and electrical damage to oil-filled power transformers with gas ratios obtained by chromatographic dissolved gas analysis (CDGA). Particular attention is paid to the analysis of the formation mechanisms of key gases (C₂H₂, C₂H₄, CH₄, H₂, CO, CO₂) and their ratios under conditions of various types of defect formation: partial discharges, arc discharges and local overheating. Taking into account the uncertainty and overlapping of diagnostic boundaries, the need to use fuzzy logic methods and probabilistic models (in particular, Bayesian analysis) for a more reliable interpretation of gas signs is substantiated. Based on a generalization of experimental data and regulatory recommendations (including IEEE C57.104–2019 and IEC 60599), an improved approach to determining the nature of defects in the early stages of their development, including in the presence of multifactorial damage, is proposed.